Sosialisasi Penanganan Cedera Kepala Ringan Dan Keseleo Di Rumah Bagi Keluarga Balita Dan Lansia - Rasyid, Djusmadi; Hajrah, Fifit; Mustarin, Yanti; Jukarnain, Jukarnain; Suardi, Vivi Adriana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Minor head injuries and sprains are two types of injuries that frequently occur in the home, especially among vulnerable age groups such as toddlers and the elderly. Lack of public knowledge regarding the initial treatment of these injuries can result in delayed medical intervention and increase the risk of complications. This Community Service (PKM) activity aims to educate families on how to recognize, assess, and administer first aid for minor head injuries and sprains at home. The activity methods included interactive counseling, first aid simulations, discussions, and the distribution of educational media in the form of leaflets. The activity was conducted in Tamasaju Village, Takalar Regency, and involved 45 participants, consisting of parents of toddlers and family members caring for the elderly. Evaluation results showed an increase in participants' knowledge and skills in independently managing minor injuries. This activity is expected to increase family preparedness and reduce the risk of adverse effects from untreated injuries.